2006
DOI: 10.1017/s0033291705006914
|View full text |Cite
|
Sign up to set email alerts
|

Deaths from all causes in a long-term follow-up study of 11583 deliberate self-harm patients

Abstract: In addition to increased risk of suicide, DSH patients are at increased risk of dying from a wide range of other causes. Possible explanations include lifestyle factors, physical disorders contributing to initial risk of DSH, and social disadvantage. The findings are relevant to clinical management and evaluation of outcome and health-care costs associated with DSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 18 publications
2
80
1
1
Order By: Relevance
“…Because suicidal behavior is the single most important risk factor for completed suicide in adolescents, the identification of precursors of adolescent suicidal behavior is of great public health importance (40). This first report of precursors of suicidal behavior in a sample at familial risk helps to identify families at very high risk of having a child with suicidal behavior and frames targets for prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Because suicidal behavior is the single most important risk factor for completed suicide in adolescents, the identification of precursors of adolescent suicidal behavior is of great public health importance (40). This first report of precursors of suicidal behavior in a sample at familial risk helps to identify families at very high risk of having a child with suicidal behavior and frames targets for prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, Spirito et al (1989) showed that up to 11% of adolescents who self-harm will eventually take their own life. Hawton et al (2006b) identified via the Oxford Monitoring System for Attempted Suicide a cohort of over 11 000 patients aged 15 who self-harmed. Follow-up over a mean period of 11 years found a death rate of 10.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1. Clinical pathways identified in the literature and assessed against the criteria of Kinsman et al 15 The first five pathways [25][26][27][28][29] were developed by British National Health Service (NHS) Trusts as a result of local clinical practice guidelines. The criteria of Kinsman et al 15 Ò Ò Ò Ò Ò Designed for young people in the local area, stops at the ED but gives some post-discharge resources Nurse-led pathway 30 Ò Ò Ò Ò Ò Ò Description of care pathway to provide a 'fast track' through the ED Hunter Area model for management of selfpoisoning 18 Ò Ò Ò Ò Ò Care pathway covers all age groups but is only for self-poisoning, not other forms of deliberate self-harm or suicidality more generally A Pathways specifically for children and young people.…”
Section: Where To Next?mentioning
confidence: 99%
“…27,28 This, coupled with the increasing number of suicidality presentations in a heterogeneous group of patients and the need to encourage community-based approaches for follow-up instead of using the ED for repeat crisis presentations, highlights the importance of implementing clinical pathways for local settings as important issues in health service and public health domains.…”
mentioning
confidence: 99%